Effects of Copolymer Structure on the Mechanical Properties of Poly(dimethyl siloxane) Poly(oxamide) Segmented Copolymers. Issue 18 (6th August 2013) - Buckwalter, Daniel J.; Inglefield, David L.; Enokida, Joshua S.; Hudson, Amanda G.; Moore, Robert B.; Long, Timothy E.
<x xml:space="preserve">Abstract</x> An investigation of the structure–property relationships of poly(dimethyl siloxane) (PDMS) polyoxamide segmented copolymers reveals the impact of oxamide spacing and PDMS molecular weight on physical properties. Varying the length of the methylene spacing between the oxamide hydrogen bonding groups in the hard segment (HS), as well as the PDMS soft segment molecular weight, provides insight into the influence on thermal and mechanical properties. Bulk polycondensation of ethyl‐oxalate‐terminated PMDS oligomers with diamines yields optically clear, thermoplastic elastomers with excellent mechanical properties. The structure–property investigation reveals optimum mechanical properties of PDMS polyoxamide segmented copolymers occur with the smallest spacing between oxamide groups in the HS. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>